1997
DOI: 10.1023/a:1005754212792
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Primary lymphomas of the central nervous system (PLCNS) of T-cell lineage are unusual. It has been suggested that T-cell PLCNS, compared to those of B-cell origin, present some differences in relation to age of presentation, gender, location of the tumor and survival. We describe two cases with T-cell PLCNS and review 22 parenchymatous T-cell PLCNS reported in the English literature. Age, gender and survival of the whole series of 24 T-cell PLCNS did not differ from that reported in large series of PLCNS where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…A prior case series and literature review suggested that pathology might be predictive of survival, with a higher frequency of long-term survivors having low-grade lymphocytic TPCNSL [23]. A larger, more recent retrospective study showed no difference in survival based on low-grade versus anaplastic histologic features [22].…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…A prior case series and literature review suggested that pathology might be predictive of survival, with a higher frequency of long-term survivors having low-grade lymphocytic TPCNSL [23]. A larger, more recent retrospective study showed no difference in survival based on low-grade versus anaplastic histologic features [22].…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…While several case series (referenced above) have made valuable contributions to the understanding of the clinical characteristics of PCNSTL, an extensive pathologic analysis/description is lacking. Several case reports and smaller case series have described the pathology and immunophenotype in varying detail 11-26 .…”
Section: Introductionmentioning
confidence: 99%
“…Primary CNS T-cell lymphoma often present with signs of increased intracranial pressure or focal neurological deficit related to the site of the space occupying lesion, much the same as a B-cell lymphoma [11]. It is often proposed however, that PCNSTL differs from PCNSBL in terms of age of presentation, gender, location of the lesion and patient survival [12]. Based on the scarcity of published data it is difficult to either support or refute the aforementioned theory completely.…”
Section: Presentationmentioning
confidence: 99%
“…The male predominance appears to be a steadfast phenomenon, however not always to the extent found in the IPCG data. The male to female ratio's in the literature for PCNSTL is in the order of 1.7 -2.2:1 and for PCNSBL 1.4 -2.0:1 [6,7,[12][13][14]. There does appear to be a trend to a slightly greater male predominance in T-cell variant compared with B-cell variant, however the significance of this in light of the much greater numbers of PCNSBL compared with PCNSTL is unknown to the current authors.…”
Section: Presentationmentioning
confidence: 99%
See 1 more Smart Citation